Granule size distribution and pasting properties of starch in normal, waxy and sweet maize kernels - Li, Wenyang; Wu, Peijin; Zhang, Dongping; Yan, Shuhui (Bangladesh Journal of Botany, 2020)
The granule size and pasting properties of starch and their relationship with quality of maize (Zea mays L.) was investigated. A clear bimodal distribution of granule sizes was found in six cultivars of maize. A number of starch granules were made up of small starch granules in kernels. Normal maize had a smaller proportion of granules <12 μm and a greater proportion of granules >12 μm, whereas sweet maize had a greater proportion of granules <12 μm and a smaller proportion of granules >12 μm. The peak, trough and breakdown viscosities were found higher in waxy maize and lower in sweet maize. The final and setback viscosities were found higher in normal maize and lower in sweet maize. The peak, trough, final and setback viscosities were significantly and negatively correlated to volume percentage of granules <12 μm and significantly positively correlated with the volume percentage of granules >12 μm.